Impact of social media for educational use and educational information-sharing on students’ academic performance - Jamalludin, Nur Hafifah; Wok, Saodah (Communication Department, Faculty of Modern Languages, Universiti Putra Malaysia, 2018)
Social media has contributed significantly to the academic field. Students are keen to use the social media as a platform to grasp academic-oriented information and materials online. As such, in light of the Social Learning Theory (SLT), this study tries to examine the impact of the social media for educational use and educational information-sharing on students’ academic performance at the International Islamic University Malaysia (IIUM). The SLT helps to explain the impact on students’ academic performance when the social media is utilised for their study. Students are able to secure a better Cumulative Grade Point Average (CGPA) when they positively use the social media for their academic-related purposes. As SLT stress on the positive rewards, thus, the social media is widely used by the students since the advantages of using it is outweigh the disadvantages. This is the main contributor to the use of the social media in the academic field. A quantitative research design is employed, using the survey method with questionnaire as an instrument for data collection. A total of 440 undergraduate students from Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS) participated in this study. The study finds that students’ academic performance is positively correlated with their social media for educational use and their educational information-sharing activities. Educational information-sharing is also found to partially mediate the relationship between the social media for educational use and students’ academic performance. Therefore, this study contributes to their utilising the social media positively in the academic field, which in turn, improves their academic performance. With this, the SLT theory holds true.